Role of tradtional food in tourist destination image building: Example of the city of Mostar - Almir Pestek; Aleksandra Nikolic (UTMS Journal of Economics, 2011)
The existence of tourist offer varieties does not imply the existence of high-quality approach to and management of a tourist destination, nor a quality development of tourist products, which is the case of the City of Mostar. Despite the existing potential, it is necessary to invest a lot of effort and mobilize several players in order to build a modern and attractive tourist destination, integrate the existing and develop new tourist products and develop the City brand. In the context of holistic approach to tourism development in the City of Mostar and its image building, it is necessary to look into the role of indigenous traditional products that can have a significant impact on the overall effects of tourist offer. The goal of the paper is to present an innovative approach to building a modern brand and tourist product of the City of Mostar, as a unique tourist destination that is founded on authentic, traditional products and the way of life. The paper is based on the research conducted in 2010 through in-depth interviews with players involved in tourism development and players in the tourism industry.
Keywords: 330; tourist destination; branding; image; traditional food